Does Coordinated Institutional Investor Activism Reverse the Fortunes of Underperforming Firms? - Song, Wei-Ling; Szewczyk, Samuel H. (Journal of Financial and Quantitative Analysis, 2003)
Wei-Ling Song, Samuel H. Szewczyk, Does Coordinated Institutional Investor Activism Reverse the Fortunes of Underperforming Firms?, The Journal of Financial and Quantitative Analysis, Vol. 38, No. 2 (Jun., 2003), pp. 317-336